(untitled) (Sirte Journal of Medical Sciences, 2025)
Healthcare workers (HCWs) are among the groups that were at the forefront of the Corona epidemic. Many of them became infected and sometimes died. Since they are among the most vulnerable to this epidemic, they were among those targeted for the Covid-19 vaccination. This an observational cross-sectional study aims to evaluate the knowledge and attitudes of health care workers at Ibn Sina Hospital in the city of Sirte regarding vaccination against the Coronavirus, and how demographic, professional, or other factors may be affected by differences in knowledge and attitudes related to acceptance of taking the Coronavirus vaccine. The study was targeted 155 participants (mean age 1.97, male 73 (47.1%), female 82 (52.9%). Those who agreed to take the vaccination were (77) and represented (49.7%). Those who did not agree to take the vaccination and answered no were (58) and represent (37.4%). There were (20) of those who were not interested and were hesitant about taking the vaccination or not, representing (12.9%) of the total number in this study.